SURGICAL AND COMBINED TREATMENT OF CANCER OF THE THORACIC ESOPHAGUS IN PATIENTS OVER 60 YEARS OLD - R. G. Badykov; V. V. Loboda; V. F. Chizhikov; R. R. Badykov; R. V. Safiullin; O. G. Yakovleva (Креативная хирургия и онкология)
Results  of  surgery  performed over  a 15-year  period  on  328  patients over  60  years old with cancer  of the  thoracic  esophagus are analyzed. Concomitant diseases, results  of functional observation are reported. Data  of surgical and  combined treatment of cancer of  the  esophagus are  presented.   Types  of  operation,  modification of  resection and esophagoplasty are considered. Direct and remote results of treatment are considered.